Ultrasound-mediated ocular delivery of therapeutic agents: a review. (3rd April 2017) - Lafond, Maxime; Aptel, Florent; Mestas, Jean-Louis; Lafon, Cyril
ABSTRACT: Introduction : Due to numerous anatomical and physiological barriers, ocular drug delivery remains a major limitation in the treatment of diseases such as glaucoma, macular degeneration or inflammatory diseases. To date, only invasive approaches provide clinically effective results. Ultrasound can be defined as the propagation of a high-frequency sound wave exposing the propagation media to mechanical and thermal effects. Ultrasound has been proposed as a non-invasive physical agent for increasing therapeutic agent delivery in various fields of medicine. Areas c overed : An update on recent advances in transscleral and transcorneal ultrasound-mediated drug delivery is presented. Efficient drug delivery is achieved in vitro, ex vivo and in vivo for various types of materials. Numerous studies indicate that efficacy is related to cavitation. Although slight reversible effects can be observed on the corneal epithelium, efficient drug delivery can be performed without causing damage to the cornea. Expert o pinion : Recent developments prove the potential of ultrasound-mediated ocular drug delivery. Cavitation appears to be a preponderant mechanism, opening a way to treatment monitoring by cavitation measurement. Even if no clinical studies have yet been performed, the promising results summarized here are promoting developments toward clinical applications, particularly in assessing the safety of the technique.